Diversity of Odonata (Insecta) in Rural and Urban Wetlands of Coimbatore, Tamil Nadu, India - Vignesh, K. Dej; Manivannan, S. (Indian Forester, 2021)
A study was conducted to assess the diversity of odonata in the rural and urban wetlands of Coimbatore, Tamil Nadu, India from August 2018 to January 2019. A total of 4 wetlands from rural and urban were surveyed with a total of 8 families of 32 genera and 45 species were recorded. Among them, 8 families of 21 genera and 26 species from Kallar a tributary stream and 4 families of 20 genera and 25 species from Ukkulam lake of rural whereas 4 families of 15 genera and 18 species from Singanallur lake and 3 families of 9 genera and 10 species from Kurichi lake of urban. Among the anisopterans, Brachythemis contaminata (Fabricius, 1793) was abundant in the urban lakes, Pantala flavescens (Fabricius, 1798) in the rural stream and Diplacodes trivialis (Rambur, 1842) in the rural lake whereas in the zygopterans, Neurobasis chinensis (Linnaeus, 1758) dominated in the rural stream, and Ischnura aurora (Brauer, 1865) dominated over the lakes.